2017
DOI: 10.1016/j.giq.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

What drives fidelity to internet voting? Evidence from the roll–out of internet voting in Switzerland

Abstract: To date, most of our knowledge regarding individuals' propensity to internet vote comes from cross-sectional survey data. In this paper we try to break new ground by tracking individuals' actual behaviour over time. Specifically, we analyze citizens' choice of voting channel by exploiting a unique longitudinal dataset -the Canton of Geneva's vote registry database. Our aim is to explore patterns in the propensity to use internet voting among eligible voters. To this end, we first mine the registry data to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…There are examples where such direct democracy has not had a significant impact on participation rates, such as in Switzerland where the voting turnout was 48.4 per cent in 2015 (Lucchi, 2017). Furthermore, there are studies that have indicated that internet voting does not have a significant influence on turnout rates (Germann and Serdült, 2017) and older citizens are more inclined to be loyal to internet voting than younger citizens, contradicting the literature (Mendez and Serdült, 2016). The contradicting findings indicate that the topic is still developing, which indicates that further research is desirable, and the results in a developing country could show significant differences.…”
Section: E-government and Nepotismmentioning
confidence: 87%
“…There are examples where such direct democracy has not had a significant impact on participation rates, such as in Switzerland where the voting turnout was 48.4 per cent in 2015 (Lucchi, 2017). Furthermore, there are studies that have indicated that internet voting does not have a significant influence on turnout rates (Germann and Serdült, 2017) and older citizens are more inclined to be loyal to internet voting than younger citizens, contradicting the literature (Mendez and Serdült, 2016). The contradicting findings indicate that the topic is still developing, which indicates that further research is desirable, and the results in a developing country could show significant differences.…”
Section: E-government and Nepotismmentioning
confidence: 87%
“…To do so, the voter must download an application available on the Åland e-Government website and then verify the vote using a QR code which has been sent via the i-Voting system as a receipt/proof of casting a vote. This process is quite similar to the ones followed elsewhere in Estonia [15,18], Switzerland [10,16] or Norway [8,11]. Besides, the law prescribes the Government of Åland to "arrange for verification of the votes in the electronic ballot box in order to ensure that they have been registered as intended, that they have been stored as they were registered and that they have been counted as they were stored.…”
Section: Verification Methodsmentioning
confidence: 94%
“…On the voter side, scholars have compared the sociodemographic characteristics and policy positions of online and offline voters (Alvarez et al 2009;Mellon et al 2017;Mendez & Serdült 2017;Vassil et al 2016), the extent to which Internet and paper-based voting are habit forming (Solvak & Vassil 2018), and explored the impact of i-voting on turnout (Germann & Serdült 2017;Goodman 2014) and residual vote rate (Germann 2020). There is also some, albeit limited, evidence that voters' likelihood of voting online might be influenced by news consumption and political activism (Trechsel et al 2007;Vassil & Weber 2011).…”
Section: Campaigning and Votingmentioning
confidence: 99%